Electric field dissociation of H-2(+): close-coupled scattering calculations - Leach, C; Child, MS; Manolopoulos, D (1999)
Close-coupling scattering calculations have been carried out to predict the magnitude of electric fields required to dissociate specific vibration-rotation levels in H2+. Results for electric fields up to 40 kV cm-1, which may dissociate levels up to 25 cm-1 below the dissociation limit, are presented. The results are used to simulate spectra which are compared with experimental spectra. A method for extracting the eigenphase sum from a coupled channel scattering calculation is described in the appendix and used in the calculations. © 1999 Taylor and Francis Ltd.